Racket programming the fun way : from strings to Turing machines - Stelly, James W. (No Starch Press, 2021)
"An introduction to Racket, a functional programming language, that exposes readers to imperative and logical programming through a series of fun applications, such as solving Sudoku puzzles and creating their own calculator. It also teaches various programming techniques, from writing statistical models to creating interactive GUIs"--